Optical properties of p-Dichlorobenzene - Manghi, E. M.; Caroni, C. A. de; Rodriguez de Benyacar, M.; Jimenez de Abeledo, M. (International Union of Crystallography, 1967)
Fil: Manghi, E. M. Comisión Nacional de Energía Atómica; Argentina